Medicinal plants of the upper Aswa River catchment of northern Uganda - a cultural crossroads - Eliot T. Masters (BMC, 2023)
Abstract Background This paper presents a comparative inventory of medicinal plant taxa and their uses by smallholder farming communities of four cultures in the Aswa River catchment of northern Uganda, situated in the eastern Sudanian savanna parkland ecotype of sub-Saharan Africa. The purpose of the study was to document the ethnobotanical use of medicinal plants by the Lango, Acholi, Teso (Atesot) and Ethur (jo Abwor), in an historical moment before civil conflict and mass displacement of the respondent communities disrupted the inter-generational transmission of traditional technical knowledge within the study area. Methods Following community consultations in four districts of northern Uganda during 1999-2000, interviews were conducted with holders of specialist knowledge on plants used as medicine on basis of a plant specimen allocated a voucher number and identified by the national herbarium. Use reports reflecting specific medicinal applications were compiled in aggregate to obtain a Relative Importance Index ranking. The commonality of medicinal taxa cited between each cultural interface was assessed by the Jaccard Index of Similarity, and the similarity of specific medicinal usage by taxon using Rahman's Similarity Index. Results The data collected from 112 respondents comprise 280 medicinal use reports describing 263 applications for 62 medical conditions, citing 108 taxa from 44 botanical families of which Fabaceae comprised 20% of all use reports. No earlier mention could be found to corroborate 72 use reports (27% of the total), representing medicinal indications as yet undocumented, and potentially worthy of investigation. The RI values ranged between 15 and 94%, with 13 taxa having RI values above 50%. The JI ratios indicate the highest degree of similarity in the plant taxa used as medicine (21%) between the Lango and Teso cultures who share a common origin; however, Rahman's Similarity Index indicates the highest similarity of specific medicinal usage by taxon between the Lango and Acholi, who share a common language group through cultural assimilation over time. Conclusions As a comparative study, the results imply that cultural exchange and assimilation may be a greater driver of inter-cultural similarity of ethnopharmacological use of a given taxon, as compared to shared historical origins.